Pengaruh E-Learning Readiness, Innovation, Performance Expectancy dan Perceived Usefulness terhadap Intention To Use E-Learning pada Perguruan Tinggi di Yogyakarta - Dyah Sugandini; Trestina Ekawati; Rahajeng Arundati; Holimin Holimin (Akademi Angkatan Udara, 2021)
This study aims to re-analyze the intention to use e-learning which is influenced by elearning readiness, innovation, performance expectations, and perceived benefits. perceived usefulness mediates the relationship between e-learning readiness and innovation on intention to use e-learning. This study has a sample of 31 universities in Yogyakarta. Partial Least Square is used to test the hypothesis in this quantitative study. The test results found that the intention to use e-learning was positively and significantly influenced by e-learning readiness, innovation, performance expectations, and perceived benefits. Positively and significantly perceived usefulness mediates the relationship between e-learning readiness and innovation on intention to use e-learning.